Tinjauan Hukum Keluarga Islam dan Undang-Undang Nomor 35 Tahun 2014 tentang Perlindungan dan Pemenuhan Hak Anak - M. Nur Khotibul Umam (Qolamuna : Jurnal Studi Islam, 2020)
Abstract This article discusses Islamic Family Law and Law Number 35 Year 2014 concerning Protection and Fulfillment of Children's Rights. The analysis results get two conclusions. First, in article 26 paragraph (1) and (2) of RI Law No. 35 of 2014 concerning Child Protection explains that parents have an obligation and responsibility to nurture, care for, and protect and grow and develop children according to their abilities, talents, and interests. Both are in line with Islamic law which states that parents are required to provide rights to children both immaterial and material in nature, among others; the right to be given a good name, the right to receive education, the right to earn a living, the power of inheritance inherent to every individual, the right to receive care, care and maintenance. Keywords: Islamic Family Law, Protection, fulfilment of children's rights.